Program Pembelajaran dalam Pembentukan Kompetensi Bahasa Asing dan Teknologi Informasi Siswa - Pramono, Diah Atika; Asy’ari, Hasyim; Zamroni, Afif; Haidar, M. Ali (Chalim Journal of Teaching and Learning, 2022)
Based on the results of data source analysis, it is known that the foreign language competency establishment program focuses on the English and Arabic learning programs. The program is divided into co-curricular, intra-curricular, and extracurricular. Co-curricular activities stand in the form of habituation, which is the English morning program for Class X, also Muhadatsah Lughatil Arabiya and Shobahul Lughah for Class XI. Intra-curricular is filled with English and Arabic language subjects. Meanwhile, extracurricular activities include English Specialization Class and Arabic Specialization Class. The IT competency establishment program is also divided into three types of activities. Co-curricular for Class X in the form of Microsoft Office Training and 2D & 3D Design Training for Class XI. Intra-curricular is filled with learning Multimedia: Graphic Design & Video Editing for Class X and Mobile Programming learning for Class XI. IT Specialization Class is an extracurricular activity in the field of Information Technology. In addition, students also take part in workshops and competitions according to their interests. Students have mastered each competency as evidenced by portfolio results in the form of pamphlet designs, photography results, short video editing and foreign language learning videos, and also participated in a speech contest